EVALUASI KERUSAKAN JALAN DAN KINERJA JALAN MENGGUNAKAN PROGRAM KENPAVE DENGAN PERMODELAN ELASTIK DAN VISKOELASTIK PADA RUAS JALAN KLANGON TEMPEL YOGYAKARTA - Panjago, Fiki; Hadi, Muhamad Abdul (Politeknik Negeri Semarang, 2024)
Klangon - Tempel Road is one of the provincial roads in Sleman Regency,Yogyakarta. The majority of vehicles that pass through this road are heavy vehiclesfrom Semarang to Yogyakarta, including the Jogja - Bawen toll road constructionproject vehicles. The high traffic load is not matched by good road quality, causingdamage to the pavement structure. This study aims to determine the condition of thepavement and provide alternative pavement designs that can withstand traffic loadswell. Evaluation of flexible pavement was carried out using data from the DIYPublic Works Office of Housing and Energy Mineral Resources (PUPSDM DIY).The method used in this research is mechanistic-empirical method of KENPAVEprogram with elastic and viscoelastic modeling. For alternative pavement designusing Bina Marga 2017 method. The results showed that the existing pavement wasnot able to withstand the traffic load during the 10-year plan life, so an alternativedesign was needed. Two alternative pavement thickness designs based on the BinaMarga 2017 method are asphalt pavement with graded foundation layer and CTB.On the existing pavement, elastic modeling has a longer service life thanviscoelastic modeling. The first damage that occurs is permanent deformation,followed by rutting and fatigue cracking. Meanwhile, the alternative pavementproved to be able to withstand the traffic load during the plan life well. Analysis onalternative pavement shows that elastic modeling has better pavement performancethan viscoelastic modeling, with longer service life in resisting damage.